17x*6x-4*3=10

Simple and best practice solution for 17x*6x-4*3=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17x*6x-4*3=10 equation:


Simplifying
17x * 6x + -4 * 3 = 10

Reorder the terms for easier multiplication:
17 * 6x * x + -4 * 3 = 10

Multiply 17 * 6
102x * x + -4 * 3 = 10

Multiply x * x
102x2 + -4 * 3 = 10

Multiply -4 * 3
102x2 + -12 = 10

Reorder the terms:
-12 + 102x2 = 10

Solving
-12 + 102x2 = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 102x2 = 10 + 12

Combine like terms: -12 + 12 = 0
0 + 102x2 = 10 + 12
102x2 = 10 + 12

Combine like terms: 10 + 12 = 22
102x2 = 22

Divide each side by '102'.
x2 = 0.2156862745

Simplifying
x2 = 0.2156862745

Take the square root of each side:
x = {-0.464420364, 0.464420364}

See similar equations:

| 0=x^2-10x+24 | | 5(40x-260)-25(80-20x)=226 | | 13-5x+7x-19=37 | | -8n+2n=-8-7n | | 25+.10x=35+.5x | | -1(3x+-13)=37 | | 0=5(7-x)+12 | | k-8=4 | | 5x+8=7c-0 | | 1.5-(32.8)= | | 7x-3.2=5.7 | | 4-d=(-d-4) | | 9(x+4)=-5x+4 | | 5x-8+3x=18 | | 6=c-9 | | -6(1+2x)=6(2x+1)+2x | | 60-5x=135-10x | | 43m+10-26m=27 | | 4y+3=(3-y)2 | | 32+-4x=84 | | 2d+1=16-d | | -48+6x=60+10x | | 0=x^4-10x^2+24 | | a=16+a | | -7(4x-9)=-7 | | 5x*7x+7*3=8 | | (3-u)(3u+7)=0 | | 6x+18=-2x-62 | | 4(5x-10)=-40+20 | | 1.3x+2=1 | | 9x^2+11=24x | | 16x^2+3x-1=0 |

Equations solver categories